HIV antibodies in seafarers, fishermen and in other population groups in the Gdańsk Region (1993-1996) - Towiańska, A; Dabrowski, J; Rozłucka, E (Bulletin of the Institute of Maritime and Tropical Medicine in Gdynia, 1996)
In 1993-1996, serological tests for HIV were performed comprising seamen, fishermen, people travelling abroad, drug addicts, patients of National Health Service Hospitals, health workers and other groups of people from the Gdańsk Region. HIV-antibodies were determined by means of immunoezymatic method ELISA, using Abbot's test recombinant HIV1/HIV2 third generation. Positive results were verified with the aid of the specific confirmation test Western blot. All in all there were 34,911 tests made and in 40 patients (0.11%) HIV-antibodies were revealed. In the group of seafarers made of 26,988 people HIV-antibodies were detected in 14 men (0.05%): 11 seamen and 3 deep-sea fishermen. The group of people travelling abroad consisted of 4269 subjects, and out them 6 men (0.18%) and one woman (0.12%) were seropositive. Out of 137 people from the group of risk-drug addicts taking narcotics intravenously-8 men (8%) and one women (2.7%) were infected. In the group of 2442 National Health Service patients, HIV-antibodies were noted in 5 men (0.31%) and one women (0.12%). Out of 172 health service workers examined nobody was infected. The group defined as "other subjects", was composed of 703 men, out which 2 were seropositive (0.28%) and 200 women-2 of them had HIV-antibodies (1.0%). The majority of seropositive subjects were men, 35 of them; there were 5 seropositive women.